THE RELATIONSHIP BETWEEN CONTROL ENVIRONMENT AND PERFORMANCE OF POST BANK AT KANUNGU AND NTUNGAMO DISTRICT BRANCHES. A CROSS-SECTIONAL STUDY. - Semanda Junior, Richard; BEINEBYABO, ADRIAN; Sendagi, Mohammed (Student's Journal of Health Research Africa, 2024)
Background. An effective control environment is where competent people understand their responsibilities, and the limits to their authority and are knowledgeable, mindful, and committed to doing what is right and doing it the right way. The control environment encompasses technical competence and ethical commitment. This study aimed to assess the relationship between the control environment and the performance of Post Bank at Kanungu and Ntungamo. Methodology. A correlation case study design was used. The respondents were selected randomly and purposively. Primary data was collected using the Questionnaires with support from an interview guide and documentary review. Data was analyzed using the SPSS package and descriptive, correlation, and regression analyses were carried out to establish relationships between the variables. Results. The majority 28 (80%) of the respondents were males and 26 (74.3%) were at Bachelor’s degree level. 31 (88.6%) of the respondents stated that ethical values were upheld in all management decisions, 30 (85.7%) of the respondents agreed that management promotes high integrity standards, 29 (82.9%) of the respondents agreed that job description exists in the bank, 17(48.6%) of the respondents agreed that turnover rate is monitored by HR and 27 (77.1%) of the respondents stated that there is an open communication to and from HR-department as stated. Conclusion. The control environment has a significant effect on performance. This means that any efforts put in the Control environment in the form of; upholding ethical values, maintaining an approved code of ethical conduct, creating free and open channels of communication plus monitoring the turnover rate may increase performance at Post Bank. Recommendation. Management of Post Bank should strengthen the approved ethical code of conduct for the promotion of high integrity standards to avoid cases of fraud which may affect the performance of the bank.